The footprint of orthostatic hypotension in parkinsonian syndromes - Raccagni, Cecilia; Sidoroff, Victoria; Goebel, Georg; Granata, Roberta; Leys, Fabian; Klucken, Jochen; Eskofier, Björn; Richer, Robert; Seppi, Klaus; Wenning, Gregor K.; Fanciulli, Alessandra (Parkinsonism & Related Disorders, 2020)
•Orthostatic hypotension may worsen gait performance in Parkinson's disease and multiple system atrophy. •Gait impairment correlates with the fall in blood pressure upon standing. •Wearable sensors detect the impact of orthostatic hypotension on gai
Keywords: Parkinson's disease; Multiple system atrophy; Orthostatic hypotension; Gait analysis